2013
DOI: 10.1021/ac3033728
|View full text |Cite
|
Sign up to set email alerts
|

High Sensitive Immunoassay for Multiplex Mycotoxin Detection with Photonic Crystal Microsphere Suspension Array

Abstract: A novel, sensitive, and high throughput competitive immunoassay for multiplex mycotoxins was established by immobilizing the artificial antigens (Ags) of mycotoxins on the surfaces of three kinds of silica photonic crystal microsphere (SPCM) suspension arrays. The SPCMs were encoded by their reflectance peak positions. Aflatoxin B1 (AFB1), fumonisin B1 (FB1), and citrinin (CIT) spiked in the cereals were extracted, and the fluorescein isothiocyanate (FITC) labeled antibodies (Abs) of these mycotoxins were adde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
89
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(90 citation statements)
references
References 53 publications
0
89
0
1
Order By: Relevance
“…15,36 The fluorescence signal intensity was the 10 times higher than that obtained from the liquid system. 34 The comparison of the calibration curves of SPCMs with the same size diameter of glass beads was performed under the same conditions, which further demonstrated the above result ( Figure.S3).…”
Section: ■ Results and Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…15,36 The fluorescence signal intensity was the 10 times higher than that obtained from the liquid system. 34 The comparison of the calibration curves of SPCMs with the same size diameter of glass beads was performed under the same conditions, which further demonstrated the above result ( Figure.S3).…”
Section: ■ Results and Discussionmentioning
confidence: 76%
“…14,15 In this paper, we established a new aptamer-based suspension array for simultaneous detection of ochratoxins A (OTA) and fumonisin B1 (FB1) in cereal samples using SPCMs as the encoded carriers. Ochratoxins A (OTA) and fumonisin B1 (FB1) are selected as a proof-of-concept that shows the capacity of the array to adapt the aptamer for a multiplex mycotoxin assay.…”
mentioning
confidence: 99%
“…With a sandwich format, the PCBs are used for multiplex detection of a series of targets, such as tumor protein markers, [162][163][164][165][166] tumor multidrug-resistance genes, [ 163 ] heart failure and coronary heart disease biomarkers, [ 168 ] environmental toxins, [ 169 ] and so on. [ 170,171 ] The PCBs in these groups all performed satisfactorily. For example, in the detection of multiplex tumor protein markers, the results indicated that the four targets, the α-fetoprotein (AFP), carcinoembryonic antigen (CEA), carcinoma antigen 125 (CA 125), and carcinoma antigen 19-9 (CA 19-9) could be assayed with limits of detection of 0.68 ng/mL, 0.95 ng/mL, 0.99 U/mL, and 2.30 U/mL, respectively.…”
Section: Multiplex Labeling Assaysmentioning
confidence: 91%
“…However, there is still a possible disadvantage of QDs as a source of optical fluorescence because of their toxicity. To avoid this problem, Zhao et al and Deng et al have produced silica colloidal crystal beads (SCCBs) and silica photonic crystal microspheres (SPCM) as carriers for the suspension array (Figure 5b) [75,76]. Their end products generally share the common ideas: e.g., both groups have used silica nanoparticles as the fundamental material for microspheres.…”
Section: Preparation Of Cell Microarraymentioning
confidence: 99%